Growth Mindset Interventions for Underprivileged Children: Academic Achievement and Developmental Outcomes at Aseema Foundation (Grades 1-3) - Nayaka, Srikantah (Journal of Educational Research and Policies, 2025)
This study investigates the impact of growth mindset interventions on the academic achievement and personal development of underprivileged children at the Aseema Foundation. Focusing on Grade 1 and Grade 3 students, the research involved a series of workshops designed to foster a growth mindset. The study assessed changes in students' attitudes toward challenges, their academic performance, and overall engagement in learning. The results suggest that students who developed a growth mindset exhibited improved academic outcomes and a more engaged approach to learning.